A tutela processual por meio das ações edilícias em face as vícios redibitórios nos contratos eletrônicos de consumo - Silva, Adriano Fabio Cordeiro da (2009)
Is in the present, a literature survey on controversial aspects of the relations of consumption when faced with the prohibitive detection of defects in goods purchased via the Internet. Aims to understand the implications that this method of procurement brings to society in their trade relations in which, for this reason, the law, therefore, also needs to protect. We discuss here the consequences of consumer relations, with emphasis on links established between consumer and seller, electronic media show will be the differences between the Code of Consumer Protection and the Civil Code, with emphasis on posture should be taken to achieve the procedural protection by the actions of defects before edilicias prohibitive in cases of contracts consumerist character. The methodology will rest on the foundation of the doctrine without forgetting to consider the modern means of information available. To deepen the analysis of reality and appropriate contracts made by means of practicing ecommerce.